2013
DOI: 10.1016/j.renene.2013.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing measurements campaigns for an innovative calibration approach of the global horizontal irradiation estimated by HelioClim-3

Abstract: International audienceThis study explores the possibility to calibrate the estimation of the global horizontal irradiation provided by HelioClim-3, a satellite-based surface solar irradiation database (available at www.soda-is.com). The main objective of this work is to refine such an estimation whose performances differ from one site to another. A first processing of the long-term measurements provided by nine weather stations located in Provence-Alpes-Côte d'Azur Region (South France) leads to the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…In such situations where devices measuring solar radiation are scarce, other approaches must be devised for mapping the SSI in an accurate way with long-standing archives. Accurate assessments of SSI can now be drawn from images from the geostationary meteorological satellites such as the Meteosat series [6][7][8], possibly in combination with ground-based measurements [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In such situations where devices measuring solar radiation are scarce, other approaches must be devised for mapping the SSI in an accurate way with long-standing archives. Accurate assessments of SSI can now be drawn from images from the geostationary meteorological satellites such as the Meteosat series [6][7][8], possibly in combination with ground-based measurements [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The values of irradiance are calculated by means of the Heliosat model, based on satellite data processing instead of local measuring stations. The validity of this model has been accurately studied in literature: for the French region PACA, the deviation among HC3 data and ground measures is calculated between 5.3% and 8.3%, with a correlation coefficient between 0.9965 and 0.9988 [14]. Other studies can be found in Refs.…”
Section: Ghi Markov Simulationmentioning
confidence: 86%
“…This lead to a maximum ratio between P BATT and the rated capacity Cap BATT , in this paper fixed to 1/10 h as described in Eq. (14).…”
Section: Storage System Modellingmentioning
confidence: 99%
“…b. De-biasing Vernay et al 15 correct the bias with a non-linear regression model fitted on a year of groundbased GHI measurements. This procedure is not applicable here because pyranometer data are for 4 months.…”
Section: Satellite Estimationsmentioning
confidence: 99%